Genetics of Seed Yield in Clusterbean (L.) - Singh, Jaivir; Saini, M L; Lodhi, G P; Singh, V P (Annals of Arid Zone, 2016)
The generation mean analysis carried out in six generation of four crosses under two environments in clusterbean indicated the importance of addithe, dominance, additive x additive, additive x dominance and dominance x dominance type gene effects in the inheritance of seed yield per plant. Duplicate type of epistasis was also observed in the crosses HG75 x RGCI37 and Pusa Navbahar x RGC 137. The exploitation of additive and non- additive gene effects in clusterbean breeding programme has bean suggested.